Daten für die epidemiologische Altersforschung. Möglichkeiten und Grenzen vorhandener Datensätze. Ergebnisse des 2. Workshops der Arbeitsgruppe Epidemiologie des Alterns der Deutschen Gesellschaft für Epidemiologie (DGEpi) - Wurm, Susanne; Fuchs, Judith; Grabka, Markus M.; Gruber, Stefan; Linkohr, Birgit; Schmidt, Carsten; Schön, Gerhard; Strobl, Ralf; Grill, Eva (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2013)
Due to the increasing proportion of older people in the general population epidemiologists are interested in identifying which factors determine healthy ageing. For this reason within the German Society for Epidemiology we founded the working group 'Epidemiology of Ageing' in 2011. The working group organised a workshop to present useful datasets on ageing in Germany for epidemiological research. Those presented included: Study of Health in Pomerania (SHIP) The German Ageing Survey (DEAS) Surveys from the Robert Koch Institute: German Health Interview and Examination Survey for Adults (DEGS) and the German Health Update (GEDA) The German Socio-Economic Panel Study (SOEP) Cooperative Health Research in the Region of Augsburg (KORA-Age) Survey of Health, Ageing and Retirement in Europe (SHARE) Germany Claims data from statutory health insurance agencies Presentations contained a brief description of the datasets, methodologies, age-related themes, their strengths and limitations as well as their availability for secondary analysis. All presented datasets can be used for longitudinal analyses and are available to the scientific community. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Ageing research; Datasets; Epidemiology; Germany; Healthy ageing